PERLINDUNGAN HUKUM TERHADAP KONSUMEN DALAM PRAKTIK PERAWATAN KECANTIKAN (Studi Penelitian Di Sams Aesthetic Beauty Medan) - Putri, Nurhaliza; Manfarisyah, Manfarisyah; Muksalmina, Muksalmina (Fakultas Hukum Universitas Malikussaleh, 2024)
Currently, there are many illegal activities happening in several beauty clinics. Therefore, this study discusses legal protection for consumers who experience facial damage after receiving treatments at Sams Aesthetic Beauty in Medan, as well as the forms of compensation obtained by consumers who suffer such damage. This research uses an empirical juridical method with a literature review and field research approach, focusing on descriptive analysis. Based on the research findings, Sams Aesthetic Beauty Clinic provides informed consent forms or agreements as legal protection for consumers before undergoing treatments. The compensation received by consumers includes continuous consultations with doctors, and the clinic takes responsibility to provide appropriate treatments to address facial issues until the consumer's face returns to its original condition at no additional cost.